Spray drying of lactic acid bacteria: understanding cell viability and strate- gies to reduce operational costs during drying of Lactococcus lactis subsp. lactis - Moreira, Maria Tereza Cratiú (2021)
Probiotic and starter bacteria are generally dried to produce easy-to-use ingredients that are stable and flexible for applications in the food, feed and pharmaceutical industry. The overall demand for dried bacteria has increased in the context of a rapidly growing market, evidencing the need for their larger scale production. The spray-drying of bacteria enables a larger production scale than the freeze-drying currently used; energy costs are lower, and the process is sustainable. This thesis reports initially a review that aims to demonstrate the operations and thermodynamic principles that govern spray drying, then correlate them to the damage suffered by LAB cells during the spray-drying process. The particularities of spray drying that might cause LAB cell death are detailed in this review, and the conclusions may enhance future studies on ways to improve cell viability. Following, a study was done to determine strategies to reduce operational costs during drying of Lactococcus lactis sbsp. lactis. The aim of this study was to determine the best drying conditions by spray drying to produce dried LAB cultures with lower cost and high cell viability. Keywords: Spray drying. Lactococcus lactis. Spray drying parameters.